Logical Foundations of Computer Science International Symposium, LFCS 2013, San Diego, CA, USA, January 6-8, 2013. Proceedings - Artemov, Sergei; Nerode, Anil.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the International Symposium on Logical Foundations of Computer Science, LFCS 2013, held in San Diego, CA, USA in January 2013. The volume presents 29 revised refereed papers carefully selected by the program committee. The scope of the Symposium is broad and includes constructive mathematics and type theory; logic, automata and automatic structures; computability and randomness; logical foundations of programming; logical aspects of computational complexity; logic programming and constraints; automated deduction and interactive theorem proving; logical methods in protocol and program verification; logical methods in program specification and extraction; domain theory logic; logical foundations of database theory; equational logic and term rewriting; lambda and combinatory calculi; categorical logic and topological semantics; linear logic; epistemic and temporal logics; intelligent and multiple agent system logics; logics of proof and justification; nonmonotonic reasoning; logic in game theory and social software; logic of hybrid systems; distributed system logics; mathematical fuzzy logic; system design logics; and other logics in computer science.
Constructive mathematics and type theory -- Logic, automata and automatic structures -- Computability and randomness -- Logical foundations of programming -- Logical aspects of computational complexity -- Logic programming and constraints -- Automated deduction and interactive theorem proving -- Logical methods in protocol and program verification -- Logical methods in program specification and extraction -- Domain theory logic -- Logical foundations of database theory -- Equational logic and term rewriting -- Lambda and combinatory calculi -- Categorical logic and topological semantics -- Linear logic -- Epistemic and temporal logics -- Intelligent and multiple agent system logics -- Logics of proof and justification -- Nonmonotonic reasoning -- Logic in game theory and social software -- Logic of hybrid systems -- Distributed system logics -- Mathematical fuzzy logic -- System design logics.
Keywords: Computer science; Information theory; Logic design; Logic, Symbolic and mathematical; Computer Science; Mathematical Logic and Formal Languages; Arithmetic and Logic Structures; Logics and Meanings of Programs; Theory of Computation; Programming Languages, Compilers, Interpreters; Mathematical Logic and Foundations